THE EVALUATION OF ANTI-EPILEPTIC DRUGS DOSAGE IN MALNOURISHED CHILDREN: CASES IN INDONESIAN COMMUNITY OF EPILEPSY - Nialiana Endah Endriastuti; Masita Wulandari Suryoputri; Dewi Latifatul Ilma (Jurnal Farmasi Sains dan Praktis, 2022)
Anti-epileptic drug (AED) has a narrow therapeutic index of drugs that a slight increase in dosage showed toxic effects. The therapeutic response is difficult to predict in malnutrition status because the patient with nutritional deficiency have more complicated problems likes hypoalbuminemia, macronutrient and micronutrients deficiency that affected the levels of AEDs. The nutritional deficiency could be a direct and indirect cause of ineffective AEDs therapy and also recurrent epilepsy. This study aims to describe the use of antiepileptic drugs in Indonesian children with poor nutritional status. The research design was observational studies with cross sectional random sampling to evaluate the AED doses of malnutrition status in children. All information was collected by spreading electronic forms and interviewing the parents by phone. The data were analyzed descriptively. Total of 8 malnourished children mostly included in the range of ages from >2 to 12 years (n=5; 62.50%) with means 3,9±2,7 years. The study showed valproic acid was bigger used in monotherapy (n=5; 62,50%) than polytherapy with carbamazepine or sodium phenytoin and phenobarbital. The means estimation of valproic acid monotherapy concentration in females’ group (n=2; 33,33%) showed sub-therapeutics level were Cssmin 26,09±0,57 mg/L and Cssmax 64,17±1,39 mg/L, also the means in males’ group (n=2; 33,33%) of valproic acid monotherapy were Cssmin 22.07±2,71 mg/L and Cssmax 54.27±6.66 mg/L. All of them included in good clinical outcome of free seizure > 6 months.